Taking the pulse of a classroom with a gamified audience response system. (January 2022) - López-Jiménez, Juan J.; Fernández-Alemán, José L.; González, Laura López; Sequeros, Ofelia González; Valle, Begoña Moros; García-Berná, José A.; Idri, Ali; Toval, Ambrosio
Highlights: Gamified classroom response increase student's performance. Badge events in gamified classroom response system (CRS) produce heart rate increases. Students are satisfied using gamified CRS. Abstract: Background and objective: This paper presents an empirical study of a gamified mobile-based assessment approach that can be used to engage students and improve their educational performance. Method: A gamified audience response system called G-SIDRA was employed. Three gamification elements were used to motivate students in classroom activities: badges for achievements to increase engagement, points to indicate progression and performance in the subject and ranking for promoting competitiveness. A total of 90 medical students in a General and Descriptive Anatomy of the Locomotor System course were taught using G-SIDRA in the academic year 2019/2020. Smart bracelets were configured to collect heart rate measurements from 30 students with the aim of evaluating the impact of the gamification elements. The control group consisted of a sample of 110 students enrolled on the same course in the academic year 2016/2017 using non-gamified SIDRA. Results: Statistically significant differences were found between multiple choice questions (MCQ) scores obtained by using SIDRA and G-SIDRA in the four experiments (U = 1.621, 50, p  < 0, 01 for Exp1; U = 1.950, 00, p  < 0, 01 for Exp2; U = 955, 00, p  < 0, 01 for Exp3; U = 2.335, 00, p  < 0, 01 for Exp4). In the students' final exam grades, statistically significant differences between students that used G-SIDRA as opposed to SIDRA (T(157) = 3.992; p  = 0.044) were obtained. Concerning gamification elements, statistically significantly differences were found in comparing the pulse increases after and before the badge event in the four experiments (U = 2.484, 00, p  = 0, 038 for Exp1; U = 2.109, 50, p  = 0, 046 for Exp2; U = 1.790, 50, p  = 0, 025 for Exp3; U = 1.557, 0, p  = 0, 048 for Exp4). However, there are not statistically significant differences between the pulse increases after and before the ranking event in the four experiments. In a 5-point Likert-type scale, the students expressed satisfaction with G-SIDRA ( M  = 4.552) and thought the system helped to better understand both theoretical and practical concepts ( M  = 4.092). Their global assessment of the G-SIDRA platform was 4.471. Conclusions: Of the three gamification elements used in the study, only badge has an effect on heart rate. Better student responses and academic performance were achieved when using G-SIDRA. Nevertheless, more research is required to evaluate the impact of the gamification elements on the motivation, engagement and performance of students. Physiological measures are promising approaches for gamification elements evaluation.